2020
DOI: 10.1371/journal.pone.0242797
|View full text |Cite
|
Sign up to set email alerts
|

Multiple spawning run contingents and population consequences in migratory striped bass Morone saxatilis

Abstract: Multiple spawning run contingents within the same population can experience varying demographic fates that stabilize populations through the portfolio effect. Multiple spawning run contingents (aka run timing groups) are reported here for the first time for striped bass, an economically important coastal species, which is well known for plastic estuarine and shelf migration behaviors. Adult Hudson River Estuary striped bass (n = 66) were tagged and tracked with acoustic transmitters from two known spawning rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Further, we found that fish size positively correlated with migration probability. This relationship to size has been previously reported for Snook, and for other migratory species including Barramundi in Australia and Striped Bass in Chesapeake Bay [ 58 , 59 , 100 , 105 ]. Both drydown duration, which affects access to freshwater prey resources, and fish size can indicate available energy resources, suggesting that energy status may serves as key factor in the decision to migrate each year.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Further, we found that fish size positively correlated with migration probability. This relationship to size has been previously reported for Snook, and for other migratory species including Barramundi in Australia and Striped Bass in Chesapeake Bay [ 58 , 59 , 100 , 105 ]. Both drydown duration, which affects access to freshwater prey resources, and fish size can indicate available energy resources, suggesting that energy status may serves as key factor in the decision to migrate each year.…”
Section: Discussionsupporting
confidence: 82%
“…The presence of distinct spawning groups has been observed in other migratory fishes. Secor et al [ 100 ] reported staggered migration timing for Striped Bass ( Morone saxatilis ) in the Hudson River, USA. Further, Koster et al [ 15 ] found differences in migration timing for Australian Grayling.…”
Section: Discussionmentioning
confidence: 99%
“…Striped bass are a popular commercial and recreational fish in coastal areas and have been historically imperiled and at times overfished (Richards and Rago, 1998;Shepherd et al, 2018). Coastal striped bass are composed of separate spawning populations (Wirgin et al, 2020) that have different distributions and movement patterns (e.g., Rulifson and Dadswell, 1995;Secor et al, 2020). These stock-specific movement patterns can vary across locations, seasons, and years (e.g., Waldman et al, 1990;Kneebone et al, 2014).…”
Section: Potential Future Directions Of Interestmentioning
confidence: 99%
“…However, Chinook salmon also exhibit variation in migration timing of smolts and adults (Fisher, 1994; Singer et al, 2020; Yoshiyama et al, 2000). Striped bass ( Morone saxatilis ) in the Hudson River Estuary migrate different distances to spawning sites and maintain these site preferences across years (Secor et al, 2020), effectively dispersing reproductive effort across multiple sections of the river. Effective management of wild populations requires understanding diversity in migratory tactics, but intraspecific variation in movement may be hard to describe while monitoring wild fishes with traditional sampling techniques, such as setlines and trapping.…”
Section: Introductionmentioning
confidence: 99%